Measuring the radar cross section of objects with electrodynamically related elements by measuring system with synthesized aperture antenna - E.S. Emelyanov; O.E. Kiryanov; V.A. Ponkin (Физика волновых процессов и радиотехнические системы, 2020)
The problem of measuring the effective scattering surface (radar cross section) by systems with a synthesized antenna aperture is considered. Using the methods of the statistical theory of detection and spatio-temporal signal processing, the regularities of the formation of the signal component of the optimal filter characterizing the magnitude of the RCS of the measured object are established. The results of mathematical modeling are consistent with the obtained laws.